How does digital inclusive finance improve the climate resilience of food production? - Liangcan Liu; Xiang Li (Frontiers in Sustainable Food Systems)
IntroductionDeveloping climate resilient agriculture is particularly important to reduce food security and climate risks in the context of frequent climate extremes disrupting food production systems.MethodsBased on the provincial panel data of China from 2011 to 2022, this paper uses dual machine learning model to explore the effect of digital inclusive finance (DIF) on climate resilience of food production (CRFP) and its transmission mechanism.ResultsDIF can significantly improve CRFP, and the conclusion is still valid after endogeneity and robustness tests. The mechanism of action shows that DIF can enhance CRFP by promoting agricultural technology innovation, agricultural industry agglomeration and agricultural socialized services. Heterogeneity analysis show that DIF has a significant effect on promoting CRFP in the eastern region, the main grain-producing areas and the regions with high digital infrastructure.DiscussionIt is necessary to strengthen the construction of digital infrastructure and improve the ecological compensation mechanism to give full play to the role of DIF in improving the climate resilience of grain production. This study provides evidence-based support for the realization of climate-smart agriculture, with policy implications for cracking the food crisis trap in low- and middle-income countries.